1989
DOI: 10.1530/jrf.0.0870573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oestradiol-17 , progesterone or bovine follicular fluid on the plasma concentrations of FSH and LH in ovariectomized Booroola ewes which were homozygous carriers or non-carriers of a fecundity gene

Abstract: Summary. The although there were significant effects of the steroids and bFF with respect to dose (P < 0\m=.\05). At 6 days after steroid implantation, no gene-specific effects were noted for the plasma concentrations of FSH although significant effects of dose of oestradiol (P < 0\m=.\01) but not progesterone were noted. Also at 6 days after steroid implantation, no gene-specific differences in the pulsatile patterns (i.e. peak frequency or amplitude) of plasma LH concentrations were noted although there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Previous studies [5,[25][26][27][28][29] have shown that plasma concentrations of FSH at some stages of the estrus cycle are higher in prolific breeds than in nonprolific breeds. Our results confirm this and show that there were fewer oocytes and follicles in the Yunling black goat compared with the Boer goat, suggesting that FSH level is directly associated with litter size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [5,[25][26][27][28][29] have shown that plasma concentrations of FSH at some stages of the estrus cycle are higher in prolific breeds than in nonprolific breeds. Our results confirm this and show that there were fewer oocytes and follicles in the Yunling black goat compared with the Boer goat, suggesting that FSH level is directly associated with litter size.…”
Section: Discussionmentioning
confidence: 99%
“…Booroola ewes have been reported to have up to 25% higher progesterone concentrations than ordinary Merino ewes during the midluteal phase of the estrous cycle, but this difference was not significant [12] because of the small sample size. In the follicular phase of the estrous cycle induced by prostaglandin F 2␣ , there were no gene-specific differences in concentrations of progesterone [13][14][15]. No differences were found in ovarian secretion rates of immunoreactive inhibins around luteolysis or in daily plasma concentrations throughout the estrous cycle, as measured by the Monash RIA [14].…”
Section: Introductionmentioning
confidence: 91%
“…More recently, plasma inhibin A concentration was determined using a specific two-site ELISA during the follicular and early luteal phases in ewes with an ovarian autotransplant, but no differences were noted between genotypes [13]. FSH and LH concentrations in plasma were not different between genotypes after treatment of ovariectomized ewes with estradiol, progesterone, or bovine follicular fluid, indicating the sensitivity of the hypothalamic-pituitary axis to ovarian hormones are similar for Booroola and ordinary Merino ewes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Rats received a single implant of approximately 1.8 cm with an internal diameter of 3.35 mm (Chen et al 2001). Ewes received 2 implants based on previous results with implants containing oestradiol (McNatty et al 1989). Oocytes and follicular debris were removed from the cells using a micro-glass pipette.…”
Section: Collection Of Granulosa Cellsmentioning
confidence: 99%